Efeito do desempenho motor nas habilidades funcionais em crianças e adolescentes com TDAH - Cristiani Junqueira (2021)
ADHD is defined as a neuropsychobiological disorder that affects neurodevelopment, involving a persistent pattern of inattention, hyperactivity and impulsivity. Children with ADHD have deficits in executive functions that are anatomically and functionally linked to motor areas, thus justifying the motor changes in 30 to 50% of children with the disorder. Motor deficits can, in the course of development, have an unfavorable effect on the quality of life and functionality of the child in the family, educational and social contexts. The aim of the present was to investigate the effect of motor performance on functional abilities in children and adolescents with ADHD. Twenty-four children and adolescents participated in this study, 19 males and 5 females, with a mean age of 11.62 ± 2.16 years, diagnosed with ADHD. The Movement Assessment Battery for Children - MABC was used to assess motor performance. -2 and for assessment of functional abilities the Pediatric Assessment of Disability Inventory Computerized Adaptation PEDI-CAT. Linear regressions were conducted between the total MABC-2 score and each of the functional skills domains. The results show that motor performance can predict the functional abilities of daily activity, mobility and responsibility, but in relation to social/cognitive functional abilities there was no significant effect.